Analysis of phlebotomy blood losses in neonates in a tertiary care hospital - Agrawal, Amit; Goyal, Shweta (Indian Journal of Child Health, 2017)
Introduction: Blood loss due to laboratory testing is greatest for the most premature neonates with very low birth weight who require many weeks of intensive support and monitoring. Objective: The purpose of this study was to find out the volume of blood withdrawn for analytical purposes in neonates. Design: Retrospective chart analysis Setting: Neonatal intensive care unit (NICU) of a tertiary care teaching hospital of central India Participants: Neonates admitted to NICU over a period of three months. All medical records of recruited patients were reviewed and amount of blood withdrawn for analytical purposes was recorded. Intervention: None Main Outcome Measures: The amount of blood overdrawn per test and blood overdrawn per newborn. Results: A total of 153 neonates were admitted to the NICU during the study period. A total of 684 samples were performed, corresponding to 4.47±3.36 (range 1-17) per neonate. The mean volume of blood removed was 9.38 ml ± 8.8 ml per newborn (range 1 -51 ml). The amount of blood withdrawn was inversely proportional to the gestational age and birth weight i.e., neonates less than 32 weeks gestation and those with birth weight <1500 gm had statistically significant more phlebotomy loss (p<0.0001). The amount of blood withdrawn per test was significantly more than required by laboratory. Conclusion: The volume of blood sampled in our NICU was higher in neonates with low birth weight and lesser gestational age. The amount of blood overdrawn per test was much higher than required by laboratory.